AACN critical care procedures performance evaluation checklists - Lynn-McHale, Debra J.; Carlson, Karen K.; American Association of Critical-Care Nurses (Philadelphia : W. B. Saunders, 2001)
This CD-ROM provides checklists covering all of the procedures found in the AACN Procedures Manual for Critical Care, 4th edition
System requirements : Windows ; Windows 95, Windows 98, or Windows NT 4.0, 486 or Pentium processor-based PC, 16 MB RAM, 10 MB of available hard disk space, CD-ROM drive
System requirements : Macintosh ; Apple Power Macintosh or compatible computer, MacOS version 7.6.1 or later, 16 MB RAM, 10 MB of available hard disk space, CD-ROM drive
Keywords: Critical Care -- methods; Nursing Care -- methods